Diagnostic value of procalcitonin, C-reactive protein and leukocyte count in detecting acute appendicitis in paedi-atric patients - a single center experience - Sanimir Suljendić; Almira Ćosićkić; Azra Hadžić-Kečalović; Denis Žigić (Medicinski glasnik, 2024)
Aim: To evaluate diagnostic reliability of accessible laboratory findings in recognition of acute appendicitis (AA). Methods: A retrospective study included children aged 0-15 years with abdominal pain that lasted less than 5 days with at least two of the signs/symptoms - abdominal pain, tenderness of the lower right quadrant of the abdomen, "return" sensitivity of the abdomen to palpation, loss of appetite, nausea, vomiting, body temperature>37.2°C. Values of procalcitonin (PCT), C-reactive protein (CRP) and the leukocyte count were analyzed in the peripheral blood. Results: Among 114 children, 63 (58.2%) were boys and 50 (41.8%) girls; median age of 9.5 years. Elevated values of PCT were found in 74 (65.5%), CRP in 94 (83.1%), and leukocytes in 78 (69%) (65%) children. Almost uniform significance in the recognition of AA was found for pathological values of PCT and CRP with sensitivity of 65% and 83% and diagnostic accuracy of 63% and 59%, respectively, but somewhat lower sensitivity for leukocytes, 61%. A very high predictive value of 98% for PCT and CRP, and PCT with leukocytes was found; CRP with leukocytes had a negative predictive value of 100%. Conclusion: PCT values have significant sensitivity, specificity and diagnostic accuracy in recognizing AA, while CRP and leukocytes, with high sensitivity, as non-specific markers can be a significant support for clinical assessment in the timely diagnosis of AA.
Keywords: appendix; diagno-sis; inflammation; predictive value of tests